Measuring the Financial Stability for a Sample of Commercial Banks Registered in the Iraq Stock Exchange for the period from 2006 to 2010 - Tawfeq, Hozan T. (Humanities Journal of University of Zakho, 2015)
The subject of financial stability acquires of great importance in the banking sector, especially in the current period in which the world has witnessed the collapse and bankruptcy of many banks. The research aims to measure the stability of commercial banks registered at the Iraq securities exchange through the annual reports of the banks surveyed from 2006 to 2010, the research sample included (10) commercial banks, covering an important part of the Iraqi banking sector, also to find out the ability of the Z-Score pattern to give an integrated image of the banking and financial stability, the research has come to set of conclusions and recommendations, the most important conclusion is that there is no difference between large banks and small banks in terms of financial stability in the financial and banking Iraqi environment, as the research recommends the need for the surveyed banks do exercise their activities properly and that the rules and instructions correctly applied so as not to interfere in the case of financial instability.